2010
DOI: 10.1074/jbc.r110.117531
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Polymerase: Structural Insights into Replication and Host Adaptation Mechanisms

Abstract: The heterotrimeric RNA-dependent RNA polymerase of influenza viruses catalyzes RNA replication and transcription activities in infected cell nuclei. The nucleotide polymerization activity is common to both replication and transcription processes, with an additional cap-snatching function being employed during transcription to steal short 5-capped RNA primers from host mRNAs. Cap-binding, endonuclease, and polymerase activities have long been studied biochemically, but structural studies on the polymerase and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
164
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(165 citation statements)
references
References 90 publications
0
164
0
1
Order By: Relevance
“…This allowed us to specifically label the 5′ end of the viral transcript (acceptor) and examine its fate during cap transfer. In the absence of CTP, 7 GpppG, part of transcripts (ca. 20%) was converted to a BAP-resistant 17-mer (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This allowed us to specifically label the 5′ end of the viral transcript (acceptor) and examine its fate during cap transfer. In the absence of CTP, 7 GpppG, part of transcripts (ca. 20%) was converted to a BAP-resistant 17-mer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here we report a unique cap-snatching mechanism by which the yeast double-stranded RNA totivirus L-A furnishes its transcript with a cap structure derived from mRNA. Unlike influenza virus, L-A transfers only m 7 Gp from the cap donor to the 5′ end of the viral transcript, thus preserving the 5′ α-and β-phosphates of the transcript in the triphosphate linkage of the final product. This in vitro capping reaction requires His154 of the coat protein Gag, a residue essential for decapping of host mRNA and known to form m 7 Gp-His adduct.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The V14I mutation is located on the α-helix in the N-terminal domain of PA (Fig. 2a), which cleaves 10-15 nucleotides (nt) downstream of the 5΄-terminal 7-methyl- guanosine cap of the pre-mRNA (Boivin et al, 2010;Fodor et al, 2002;Hara et al, 2006). Since this α-helix is in the proximity of the active site of the N-terminal domain of PA, it may play a role in enhancing the stability of the active site by altering the steric hindrance.…”
Section: Modeling Of Mutiply Mutated Rna Polymerasementioning
confidence: 99%
“…More recent studies have shown a differential dependence on a specific importin-alpha proteins, with avian IAVs dependent on importin-alpha3 and mammalian IAVs dependent on importin-alpha7 [142]. Regardless, once in the nucleus, mRNA and complementary viral RNA (cRNA) are transcribed from the vRNA template Viral transcription of the viral mRNAs is mediated by the heterotrimeric RdRp (PB1, PB2 and PA), NP and host-derived components (described below) [143,144]. First the RdRp complex recognizes and binds to newly transcribed host cellular mRNAs containing a 5' cap in the nucleus [145,146].…”
Section: Transcriptionmentioning
confidence: 99%